Assessing the Potential for MRSA and VRSA Transmission among Food Handlers in Dhamar: A Critical Need for Intervention (Thamar University Journal of Natural & Applied Sciences, 2025)
Scientific background: Food handlers carrying Staphylococcus aureus on their noses mainly contribute to food contamination. Antibiotic resistance in S. aureus represents a significant public health concern. The drug of choice, Vancomycin, has become more popular as the rate of MRSA has increased. Consequently, VRSA has begun to emerge. This study aimed to assess the distribution of S. aureus nasal carriage and its antibiotic susceptibility patterns among food handlers at Dhamar restaurants in Yemen. Method: A cross-sectional study was conducted in Dhamar City, Yemen, between January and February 2023, collecting nasal swabs from 100 food handlers. Standard bacteriological techniques were applied to inoculate the collected swabs on mannitol salt agar to identify and isolate S. aureus. Researchers used the Kirby-Bauer disk diffusion method to test the antimicrobial susceptibility of methicillin and Vancomycin. Results: S. aureus colonized 44 (44%) of the 100 nasal food handlers working in Dhamar, Yemeni restaurants. Among the 44 S. aureus isolates, 6 (13.6%) were resistant to Vancomycin (VRSA), and 23 (52.3%) were resistant to methicillin (MRSA). A correlation was not observed between the nasal carriage rate of S. aureus and specific food handler variables. In conclusion, the high nasal carriage of S. aureus, including MRSA and VRSA, among food handlers poses significant risks to consumers, underscoring the need for strict policies, routine screening, and effective management to ensure food safety and control resistant bacteria.